Development of Genially-based interactive learning media to enhance junior high school students’ mathematical literacy and mathematical disposition - Rio Tri Hartanto; Anton Nasrullah; Ratu Khoirotun Nisa; Shahzadi Hina (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Mathematics learning at the junior high school level continues to face various challenges, particularly the low levels of students’ mathematical literacy and mathematical disposition, which are largely caused by the limited availability of interactive learning media. Students often experience difficulties in understanding problem information, organizing concepts, and constructing solutions systematically, especially in the topic of integers. This study aimed to develop Genially-based interactive learning media for the topic of integers for seventh-grade junior high school students and to evaluate its validity and practicality. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The developed media were validated by a media expert, a subject-matter expert, and a language expert, and their practicality was tested through small-scale and large-scale trials involving junior high school students. The validation results indicated that the learning media achieved average scores of 86% from the media expert, 93% from the subject-matter expert, and 98% from the language expert, all of which fell into the “very valid” category. Meanwhile, the practicality test results showed scores of 86% in the small-scale trial and 84% in the large-scale trial, both of which were categorized as “very practical.” Based on these findings, the Genially-based interactive learning media were considered feasible for use and demonstrated potential to support the development of junior high school students’ mathematical literacy and mathematical disposition. This study contributes to mathematics education research by providing empirically validated evidence on the feasibility of Genially-based interactive learning media as an effective alternative to support students’ mathematical literacy and mathematical disposition, particularly in the topic of integers.